2012
DOI: 10.5688/ajpe76344
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Structured Clinical Examination to Assess Problem-Based Learning

Abstract: Objectives. To compare pharmacy students' performance on an objective structured clinical examination (OSCE) to their performance on a written examination for the assessment of problem-based learning (PBL); and to determine students' and faculty members' perceptions of OSCEs for PBL evaluations. Design. Four OSCEs were added to the written examination to assess 4 PBL cases in a third-year pharmacotherapy course. OSCE scores were compared to written examination scores. Faculty members evaluated student performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 30 publications
0
42
2
2
Order By: Relevance
“…Although the satisfaction about the appropri ateness of the exam environment was somewhat low, this can be improved in future by dividing the student's exam into two sessions to decrease the number of students per each exam session, these finding show that OSCE can be applied in simplified and low cost mode and in a valid manner. The students were satisfied about the difficulty of the exam, students' views on fairness and difficulty of the exam may not necessarily be consistent with other published literature 20 and these findings must not be interpreted in isolation. Students was somewhat less satisfied about the time allowed to perform the exam, this problem will be taken into account in the future to increase time per each station to 15 minutes that used in some pharmacy OSCE programs, but it may be related to students' naivety to this method of assessment where it has been shown that many students felt that the OSCE was a highly anxietyproducing exam, more stressful than other types of examinations and should be introduced earlier in the curriculum.…”
Section: Osce Student Satisfactionmentioning
confidence: 54%
See 3 more Smart Citations
“…Although the satisfaction about the appropri ateness of the exam environment was somewhat low, this can be improved in future by dividing the student's exam into two sessions to decrease the number of students per each exam session, these finding show that OSCE can be applied in simplified and low cost mode and in a valid manner. The students were satisfied about the difficulty of the exam, students' views on fairness and difficulty of the exam may not necessarily be consistent with other published literature 20 and these findings must not be interpreted in isolation. Students was somewhat less satisfied about the time allowed to perform the exam, this problem will be taken into account in the future to increase time per each station to 15 minutes that used in some pharmacy OSCE programs, but it may be related to students' naivety to this method of assessment where it has been shown that many students felt that the OSCE was a highly anxietyproducing exam, more stressful than other types of examinations and should be introduced earlier in the curriculum.…”
Section: Osce Student Satisfactionmentioning
confidence: 54%
“…In spite of some variations in average scores between individual stations that were found for some areas, the overall results were more similar than expected, this finding is consistent with another study that compared between different OSCE stations. 20 OSCE achievements among third and fourth groups were similar, indicating the consistency of OSCE design even with different number of stations used.…”
Section: Individual Osce Stations Achievementmentioning
confidence: 68%
See 2 more Smart Citations
“…2 Literature supports the use of OSCEs to evaluate clinical knowledge and competence, professional judgment, problem-solving skills, and interpersonal and communication skills. [6][7][8] The combination of the OSCE with standardized board examinations has the potential to become the gold standard for measuring physician competence. 9 For years, physicians have used OSCEs as part of their licensing process.…”
Section: Introductionmentioning
confidence: 99%